SOME WAYS OF PRODUCTION PROCESS OF LIVE PLAGUE VACCINE AND TECHNIQUES OF EVALUATION THE IMMUNOGENICITY (REVIEW) - Zh. A. Konovalova; A. G. Atlas; V. I. Dubrovina (Acta Biomedica Scientifica)
The modern findings of scientific research in a live plague vaccine range such as production antibiotic-resistant subcultures of the vaccine strains, design of the low-development of reaction producers vaccine strains, production of oral (tablet) preparation are represented in the review. Some techniques of production improvement live plague vaccine are formulated: stabilization of a number alive microbial cells in a inoculation dose of a license vaccine by decreasing of cultivation temperature mode from 27 °C till 21°С, concentration of microbial cells in ampoule from (5-10) × 1010 till (1-4) × 1010 per 1 ml, reduction freezing-drying step from 28 till 18 h, decreasing of amount dose in ampoule from 100-125 till 20-50 and furthermore acceleration of production process of microbial cells concentrate (fermentation in the bioreactor, tangential microfiltration) and formulation combined (meat-soya nutritious base) medium and conditions of their preparation (time reduction enzymatic hydrolysis from 14 till 3 days). The tendenceis of refinement of a technological process of equipment link were researched, such as using bioreactors instead of apparatusfor a cultivation microbesShesterenko, disposable bags Flexboy, which are allowed to eliminate the application of glass bottles and operation of a bottle assembling, also using of robotizing sublimation installations for drying of a liquid form of live plague vaccine, which are allowed to exclude utilization of low-temperature refrigerators. Beside of regulating estimation method of immunogenicity (calculation of effective immunizing dose) and quantitative account of a phenomenon of survival white mice the cyto-enzymochemical and morphometric rates are suggested to estimate the quality of ultimate product live plague dry vaccine, changes of those are charactering immunologic activity and state of mobilizing and bactericidal abilities of a organism phagocyte system cells.